Pengenalan Perkembangan Organ Reproduksi perempuan pada anak Pendidikan Sekolah Dasar di MGI Ciamis - Sandriani Sandriani; Rosidah Solihah; Aulia Ridla Fauzi; Metty Nurherliyany (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: The development of the reproductive organs is an important part of a child’s growth and development process, which should be introduced from primary school age onwards through an educational approach appropriate to the child’s stage of development. A lack of understanding among children regarding physical changes, the function of the reproductive organs, and the importance of maintaining the hygiene and health of the reproductive organs may increase the risk of inappropriate behaviour towards their own bodies. Therefore, preventive measures are required through child-friendly and easily understandable reproductive health education. Objective: This community service initiative aims to educate elementary school-aged children about their own bodies in a healthy, accurate, and developmentally appropriate manner, as well as to provide elementary school-aged children—particularly girls—with an appropriate understanding of and exposure to reproductive health education, so that they develop an early awareness of their body parts, the basic functions of their reproductive organs, and the importance of maintaining personal hygiene and safety.Methods: The methods used in this community service activity included interactive learning activities such as lectures, discussions, educational games, question-and-answer sessions, and visual aids in the form of illustrations of the reproductive organs tailored to the characteristics of children. Results: The results of the activity showed changes in the participants’ behavior regarding their understanding of the female reproductive organs, physical changes leading up to puberty, and behaviors related to personal hygiene. The children were able to name the body parts that need to be kept clean, understand the concept of bodily privacy, and showed enthusiasm throughout the learning process. Conclusion: This community service activity can be considered effective as a preventive and promotive measure in fostering reproductive health literacy from an early age, particularly in supporting the healthy growth and development of children who are self-confident and have a healthy body image.